2018
DOI: 10.1080/00343404.2018.1548764
|View full text |Cite
|
Sign up to set email alerts
|

Territorial Cohesion Cities: a policy recipe for achieving Territorial Cohesion?

Abstract: This article discusses the role of medium towns as crucial anchors in achieving the policy goal of Territorial Cohesion. It highlights the need to counterbalance market trends to favour the continuous channelling of investment and people into larger metropolitan areas, by way of pro-active measures focused on attracting investment into medium towns, and as an alternative to dispersing public and private investment in lagging territories. Iberian and Nordic cases are examined in order to illustrate the possibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 26 publications
0
23
0
3
Order By: Relevance
“…Since joining the EU, in 1986, Portugal has received financial support from EU funds to promote its territorial development process, in particular through the EU Cohesion Policy [5,52]. In synthesis, from the intervention's strategic priority, during the first four EU Cohesion programming periods (1989-2013), the bulk of the EU funding was allocated to (i) modernize accessibility and socioeconomic infrastructures; (ii) reinforce economic competitiveness; and (iii) support human capital and employment [53].…”
Section: Portugal 2020: Contributions To Sustainable Development?mentioning
confidence: 99%
“…Since joining the EU, in 1986, Portugal has received financial support from EU funds to promote its territorial development process, in particular through the EU Cohesion Policy [5,52]. In synthesis, from the intervention's strategic priority, during the first four EU Cohesion programming periods (1989-2013), the bulk of the EU funding was allocated to (i) modernize accessibility and socioeconomic infrastructures; (ii) reinforce economic competitiveness; and (iii) support human capital and employment [53].…”
Section: Portugal 2020: Contributions To Sustainable Development?mentioning
confidence: 99%
“…Today, a balancing act between the two is still pursued (Nosek, 2017). Farago and Varro (2016) advocate pro lagging regions, whereas Medeiros and Rauhut (2018) advocate pro urban regions. Continuing arguments for pro full coverage approaches (e.g.…”
Section: Implications For Post-2020 Eu Cohesion and Regional Policymentioning
confidence: 99%
“…However, this palpable neoliberal trend, justified by an economic context dominated by a deep financial crisis (2008), can hold far-reaching negative implications for the implementation of the TA goals. Indeed, existing literature has shown that, in the past decade (at least), there have been no territorial cohesion trends at the national level, despite the positive impacts associated with EU Cohesion Policy investments in promoting territorial development in many policy arenas and territories (Medeiros & Rauhut, 2020).…”
Section: A Need For a Simple Territorial Agenda Message?mentioning
confidence: 99%
“…These dimensions differ in the way that, over time, a territorial cohesion process requires the less developed areas, in a baseline scenario, to show higher levels of development than the more developed ones. This has proved to be a particularly difficult to achieve in terms of policy goal, especially at the national territorial level (Medeiros & Rauhut, 2020). For some, the EU territorial cohesion vision builds on the counteraction or mitigation of spatial imbalances, as well as the increasing policy effectiveness aiming to maximise the exploration of territorial characteristics (Asprogerakas & Zachari, 2020).…”
Section: Territorial Cohesionmentioning
confidence: 99%